The craft of research - Booth, Wayne C.; Colomb, Gregory G.; FitzGerald, William T.; Williams, Joseph M.; Bizup, Joseph 1966- (Chicago guides to writing, editing, and publishing., 2024)
"With more than a million copies sold since its first publication, The Craft of Research has guided generations of readers at all levels to become better researchers, thinkers, and communicators. The original authors--all of them legendary teachers--believed that research is a communal activity and illustrated how to choose meaningful topics, make sound and compelling arguments, and convey these arguments effectively in writing for the benefit of other researchers. While preserving the book's proven approach to the research process, as well as its distinctive voice and general structure, this new edition recognizes the more diverse ways research is conducted and communicated today. Thoroughly revised by Joseph Bizup and William T. FitzGerald, it acknowledges that research may end in a product other than a paper--or no product at all--and includes a new chapter about effective presentations. It features new examples on contemporary research topics and accounts for new technologies used in research, including basic guidelines for appropriate use of generative AI. And it ends with an expanded chapter on ethics that addresses researchers' broader obligations to their research communities and audiences as well as systemic questions about ethical research practices. This beloved classic is now ready for a new and more diverse generation of researchers"-- Provided by publisher.